1997
DOI: 10.1097/00003446-199706000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation of Children with Minimal Open-Set Speech Recognition Skills

Abstract: The findings of this study indicate that both groups derive significant benefit from their cochlear implants. Although the mean preoperative audiograms for the implanted ears did not differ significantly for the two groups of subjects, members of the Borderline group exhibited significantly better speech recognition skills than the Traditional group during the first year after implantation. These findings suggest that the increased auditory experience of the Borderline subjects positively influenced their perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 8 publications
0
26
0
8
Order By: Relevance
“…In young children, the age at which the hearing impairment occurred, the length of auditory deprivation, and amount of experience using the implant have all been shown to play important roles in predicting outcome Miyamoto et al, 1994;Nikolopoulos, O'Donoghue, & Archbold, 1999). From recent reexamination of audiological candidacy requirements, it has also been determined that the presence of even minimal amounts of residual hearing under aided conditions before implantation can also contribute positively to success with an implant (Seghal, Kirk, Pisoni, & Miyamoto, Reference Note 2;Zwolan, Zimmerman-Phillips, Ashbaugh, Hieber, Kileny, & Telian, 1997). However, there is still a large proportion of unexplained variance in this multivariate prediction of speech perception performance .…”
mentioning
confidence: 99%
“…In young children, the age at which the hearing impairment occurred, the length of auditory deprivation, and amount of experience using the implant have all been shown to play important roles in predicting outcome Miyamoto et al, 1994;Nikolopoulos, O'Donoghue, & Archbold, 1999). From recent reexamination of audiological candidacy requirements, it has also been determined that the presence of even minimal amounts of residual hearing under aided conditions before implantation can also contribute positively to success with an implant (Seghal, Kirk, Pisoni, & Miyamoto, Reference Note 2;Zwolan, Zimmerman-Phillips, Ashbaugh, Hieber, Kileny, & Telian, 1997). However, there is still a large proportion of unexplained variance in this multivariate prediction of speech perception performance .…”
mentioning
confidence: 99%
“…This PBK test is an open-set test of spoken word recognition (also see Meyer & Pisoni, 1999) and is very difficult for prelingually deaf children when compared to other closed-set speech perception tests routinely included in the standard clinical assessment battery (Zwolan, Zimmerman-Phillips, Asbaugh, Hieber, Kileny & Telian, 1997). Children who do reasonably well on the PBK test display ceiling levels of performance on other closed-set speech perception tests that measure speech pattern discrimination skills.…”
Section: Analysis Of the Starsmentioning
confidence: 99%
“…Zwolan, Zimmerman-Phillips, Ashbaugh, Hieber, Kileney, & Telian (1997) found that children with more pre-implant residual hearing (i.e. with some auditory experience) exhibited significantly better speech recognition skills within the first year following implantation than children with less auditory experience.…”
Section: Respond What He 'S Done Is Far Greater Than What We Did mentioning
confidence: 99%